Efficiency of different miniscrew positions for maxillary incisor intrusion: A comparative cone beam study - Ahmed, Mohamed Ahmed Mohamed; AbdelAllah, Mostafa Magdi Abdelmonem; Raslan, Esmail Kamal Hewy; Gouda, Wesameldin Rafaat Ali; Dawaba, Mostafa Mohamad Mahmoud; El-Ghafar, Ibrahim Saad Abd; Ali, Ahmed Mahmoud Ahmed; Abdelmonem, Marwa Hassan (International journal of health sciences, 2021)
Aim: To evaluate the treatment efficacy of two different position of mini-implant-assisted methods to intrude the maxillary incisors using cone-beam computed tomography (CBCT). Patients and Methods: The study included 26 patients with elongated maxillary incisors and a deep bite, ranging in age from 12 to 18 years. One group received anterior mini-implants, whereas the other received posterior ones at random. The AMG used elastic chains to apply about 40 g of force per side, while the PMG used beta-titanium wires. This investigation used CBCT scans that were performed before and after an intrusion that lasted 18 weeks. Result: Significant changes in the labial inclination of all incisors, which were greater in PMG than AMG. Conclusion: Both mechanics result in increased labial tilting, but posterior mini-implants assisted maxillary incisor intrusion is greater, so it is preferred when the patient's incisors is upright position.